1999
DOI: 10.1038/sj.ijo.0800930
|View full text |Cite
|
Sign up to set email alerts
|

Obese male subjects show increased resting forearm venous plasma noradrenaline concentration but decreased 24-hour sympathetic activity as evaluated by thrombocyte noradrenaline measurements

Abstract: OBJECTIVE: To study resting forearm venous plasma noradrenaline (NA) and 24 h sympathoadrenal activity evaluated by measurements of thrombocyte NA and adrenaline (A) in obese male subjects before and after weight reduction. DESIGN: Blood samples were collected in obese subjects and in controls after an overnight fast. MEASUREMENTS: Fatness and fat distribution parameters, plasma and thrombocyte NA and A, lymphocyte b b 2 -adrenoceptor mRNA, cAMP and lymphocyte subset composition. RESULTS: Forearm venous plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Studies on in vivo ventricular function assessed by echocardiography gave mixed results; in some, improved function in ZO rat hearts [21] was found, while other authors reported a reduction in contractile function [22]. In our study, ZO rats tended to be tachycardiac in vivo; this tendency was reversed in vitro, where neurohumoral influences disappeared, suggesting for instance an increase in circulating catecholamines, which has already been observed in ZO rats [23], and in obese humans [24].…”
Section: Discussionsupporting
confidence: 51%
“…Studies on in vivo ventricular function assessed by echocardiography gave mixed results; in some, improved function in ZO rat hearts [21] was found, while other authors reported a reduction in contractile function [22]. In our study, ZO rats tended to be tachycardiac in vivo; this tendency was reversed in vitro, where neurohumoral influences disappeared, suggesting for instance an increase in circulating catecholamines, which has already been observed in ZO rats [23], and in obese humans [24].…”
Section: Discussionsupporting
confidence: 51%
“…Clearly additional studies are needed to complete our understanding of the mechanism. The finding of an inverse correlation between thrombocytic catecholamines and FM in obese subjects might, as discussed previously (35), reflect a reduction in the sympathoadrenal activity with increasing body mass index.…”
Section: Discussionmentioning
confidence: 86%
“…In 22 subjects, 12 obese and 10 lean, plasma and thrombocytic concentrations of adrenaline and noradrenaline were determined, as a measure of sympathetic activity as described previously (35). These subjects did not differ from the whole group with respect to age, height, weight, body composition, 24-hour EE, or fasting plasma leptin.…”
Section: Sympathetic Activitymentioning
confidence: 99%
“…No differences were demonstrated between normal subjects or obese subjects as regards the b 2 -adrenoceptor mRNA level and the subset composition. 10 In conclusion, we have shown that the lymphocyte GCR mRNA concentration and serum leptin concentrations are inversely correlated and both of them related to the waist ± hip ratio in a group of normal non-obese subjects. It is suggested that the decrease in GCR mRNA concentration with increasing serum leptin concentrations is a counter-regulatory response to an increased body fat content.…”
Section: Discussionmentioning
confidence: 94%